The effects of ınstrumental and symbolıc ımage dımensıons on employer attractıveness ın terms of employer brandıng - Maraşlı, Furkan (My University, 2017)
İşveren markası bir organizasyonun ‘çalışılabilecek en iyi yer’ algısı yaratma çabasıyla çalışanlarına sunduğu psikolojik, ekonomik ve fonksiyonel faydalar olarak tanımlanmaktadır. Son yıllarda birçok akademik çalışmaya konu olan işveren markasının amacı organizasyonun entelektüel sermayesine katkıda bulunabilecek potansiyel iş gücünü organizasyona çekebilmek ve organizasyonun içinde yer alan entelektüel sermayeye hâlihazırda katkıda bulunan mevcut işgücünü organizasyonun içinde tutabilmeyi kolaylaştırmaktır. Bu çalışmanın amacı enstrümantal ve sembolik imaj değerlerinin işveren marka çekiciliğine etkisini kolektivist kültüre sahip Türk toplumu üzerinde ölçmektir. Çalışma, 2016-2017 yılları arasında Türkiye’deki üniversitelerin İktisadi ve İdari Bilimler Fakültelerinde okuyan 289 son sınıf lisans, yüksek lisans ve doktora öğrencisinden elde edilen verilerin analizleriyle yapılmıştır. Anket yoluyla toplanan veriler, sırasıyla faktör analizi, güvenilirlik analizi, korelasyon ve doğrusal regresyon analizine tabii tutulmuştur. Analizler IBM SPSS 23 yapılmıştır.Araştırma bulguları en değerli sermaye olan entelektüel sermayeyi organizasyona çekmenin ve entelektüel sermayeye katkı sağlayacak mevcut çalışanları organizasyon içerisinde tutmanın önemini ve yöntemini ortaya koymuştur. Analiz sonuçlarına göre enstrümental ve sembolik imaj değerlerinin tüm alt boyutlarının işveren marka çekiciliği üzerinde pozitif yönlü etkisinin olduğu saptanmıştır. Çalışmanın; Türkiye’de işveren markası ve örgütsel çekicilik literatürüne katkı sağlanması beklenmektedir.

Employer brand is defined as functional, economic and psychological benefits and efforts provided by employment institution in order to create ‘great place to work’ perception in the eyes of prospective and existing employees. The concept has been subject to various studies in strategic human resource field in order to attract high-skilled potential employees and retain existing employees to create competitive advantage over its competitors with creating high intellectual capital asset.Present study focusses on the effects of instrumental and symbolic image dimensions of employer on employer attractiveness in terms of employer branding concept in Turkish society which have collectivistic culture. In order to test propositions, field and online survey using questionnaires was conducted on 289 last year bachelor, master and PhD students who are studying in Faculty of Economics and Administrative Sciences in Turkish universities between the years 2016-2017. Data gathered from questionnaires are analysed through IBM SPSS 23 program. Factor and reliability analysis, correlation and linear regression analysis are applied respectively in order to test hypothesis and the direction of relation between independent and dependent variables. The findings of the research revealed the importance and recipe of retaining existing high skilled employees and attracting prospective ones in order to create intellectual capital. Analysis results showed that all sub dimensions of instrumental-symbolic framework have significant positive affect on employer attractiveness. All the hypothesis are accepted and findings are consistent with the literature. Research will add contribution to existing literature and perception on employer branding and organizational attractiveness in Turkey.
Keywords: employer attractiveness; İşletme; İşveren markası; Örgütsel bağlılık; örgütsel çekicilik employer branding; Yönetim